Administrative Potential of the Personnel: Methodology of Assessment and Application - Elena Igorevna Kudriavtseva (Управленческое консультирование)
Modern socio-economic and socio-cultural conditions predicts changesof characteristics of the professional activity, including - managerial activity. It acquires a new features, differs significantly from its own classical forms. The paper characterizes a non-classical of managerial activities that necessitate revision of the concepts of managerialcapacity of human resources. Author offers to consider the typology of the managerial capacity of the paper characterizes a non-classical of managerial activities that necessitate revision of the concepts of organizational staff managerial capacity as the methodological basis of appropriate technologies of personnel management.